2012
DOI: 10.1038/nature11140
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium isotope evidence for a transition in the dynamics of continental growth 3.2 Gyr ago

Abstract: Earth's lithosphere probably experienced an evolution towards the modern plate tectonic regime, owing to secular changes in mantle temperature. Radiogenic isotope variations are interpreted as evidence for the declining rates of continental crustal growth over time, with some estimates suggesting that over 70% of the present continental crustal reservoir was extracted by the end of the Archaean eon. Patterns of crustal growth and reworking in rocks younger than three billion years (Gyr) are thought to reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(120 citation statements)
references
References 43 publications
10
110
0
Order By: Relevance
“…Although a Hadean onset has been hypothesized, the evidence for this remains equivocal (see previous section). Naeraa et al (2012) propose that the pattern exhibited by zircon data from SW Greenland indicates reworking of crust from 3.9 to 3.2 Ga, and that significant juvenile signatures with fluctuating trends after 3.2 Ga correspond to the onset of a geodynamic regime featuring arc formation and accretion (see Fig. 6).…”
Section: The Onset Of Plate Tectonicsmentioning
confidence: 99%
“…Although a Hadean onset has been hypothesized, the evidence for this remains equivocal (see previous section). Naeraa et al (2012) propose that the pattern exhibited by zircon data from SW Greenland indicates reworking of crust from 3.9 to 3.2 Ga, and that significant juvenile signatures with fluctuating trends after 3.2 Ga correspond to the onset of a geodynamic regime featuring arc formation and accretion (see Fig. 6).…”
Section: The Onset Of Plate Tectonicsmentioning
confidence: 99%
“…Several authors have concluded that these signatures are absent in Archean or even Proterozoic terranes, and that plate tectonics had not operated during these periods. Stern (2008Stern ( , 2013, Hamilton (2008Hamilton ( , 2011 1.8-2.7 Ga Bédard (2006), Rollinson (2010), Brown (2007), Keller and Schoene (2012) by 2.7 Ga Condie and Kröner (2008), O'Neill et al (2007), Korenaga (2006), Davies (2007), van Hunen and Moyen (2012) 3.0 Ga Benn (2006), Cawood et al (2006), Pease et al (2008), Richardson and Shirey (2008), Polat (2012), Dhuime et al (2012), Naeraa et al (2012) 3.3-3.5 Ga Zegers and van Keken (2001), , Smithies et al (2007), Van Kranendonk (2007), Griffin et al (2013) 4.3 Ga Harrison et al (2008) Stern (2008,2013) has adopted what is perhaps the most extreme position. He argues in a series of papers (and an excellent blog; Stern, 2013) that there was "a progression of tectonic styles from active Archean tectonics and magmatism to something similar to plate tectonics at ˜1.9 Ga to sustained, modern style plate tectonics … beginning in Neoproterozoic time" (Stern, 2008, page 265).…”
Section: The Onset Of Plate Tectonics -A Great Debate In the Geosciencesmentioning
confidence: 99%
“…However, the new plate tectonics theory had only a superficial similarity with continental drift, because all previous mobilist and fixist geodynamic theories became obsolete after the revolutionary advances that occurred in geophysics occurred during the 1960s. Plate tectonics quickly became the fundamental framework for Earth sciences, considered valid at least since 3-3.5 Ga (Condie and Kröner, 2008;Naeraa et al, 2012). In its more than 50 years of existence plate tectonics has amply proved its ability to explain within a single context the most diverse geological phenomena, and it is supported by a great deal of evidence.…”
Section: Introductionmentioning
confidence: 99%